Multi-pass, multi-bunch beam breakup for 9-cell Tesla cavities in the ERL - 陈思 黄森林 李永明 冯立文 朱凤 全胜文 刘克新 陈佳洱 (Chinese physics C, 2013)
Generally, the Energy Recovery Linac （ERL） needs specially designed high current superconducting RF cavities. In this paper, the threshold current of beam breakup for compact ERL facilities with 9-cell Tesla type cavities are investigated. The results show that it is feasible to adopt the 9-cell Tesla cavity for compact ERL test facilities with just a few cavities and beam current around 10 mA.